Dissolution of bovine pulp tissue in solutions consisting of varying NaOCl concentrations and combined with EDTA - Luis Eduardo Duarte Irala; Renata Grazziotin-Soares; Alexandre Azevedo Salles; Aline Zen Munari; Joseani Santos Pereira (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This in vitro study evaluated (1) the dissolution of bovine pulp tissue in solutions consisting of varying NaOCl concentrations and combined with EDTA; and (2) the pH of these solutions before and after the experiment. The independent variables were the concentration and the volume of the solution. Thirty bovine pulps were divided in equal fragments, resulting in 90 fragments of pulp tissue. Each fragment was immersed in one of the following solutions: 1% NaOCl (4 ml), 2.5% NaOCl (4 ml), 1% NaOCl + 17% EDTA (2 ml : 2 ml), 1% NaOCl + 17% EDTA (1 ml : 3 ml), 2.5% NaOCl + 17% EDTA (2 ml : 2 ml), and 2.5% NaOCl + 17% EDTA (1 ml : 3 ml). The test solutions were dichotomized as either able or not able to dissolve the tissue, the latter being attributed when the dissolution of the pulp tissue was not complete within 48 hours. When the samples were able to dissolve the tissue, the time required for complete tissue dissolution was submitted to statistical analysis. The pH of the solutions was measured before and after the experiment. The pH variable was dichotomized as either changed or unchanged. The results demonstrated that the NaOCl solutions combined with 17% EDTA were not able to dissolve the tissue. The t-test revealed that the 2.5% NaOCl solution presented a lower mean dissolution time than the 1% NaOCl solution (p < 0.001). The pH of the solutions with equal volumes of NaOCl and EDTA decreased in 48 hours.